Antifungal susceptibility profile of Candida species and uncommon yeasts from drug abusers with oral candidiasis - Aynaz Ghojoghi; Sadegh Khodavaisy; Ali Zarei Mahmoudabadi; Mahnaz Fatahinia (BMC Oral Health)
Abstract In Iran, there is limited information regarding the species distribution and antifungal susceptibility profiles of yeast isolates from drug addicts suffering from oral candidiasis (OC). In this study, 104 yeast isolates, including 98 Candida species and 6 uncommon yeasts, were collected from 71 drug abusers with OC. The susceptibility profiles of Candida spp. and uncommon yeasts to amphotericin B (AMB), itraconazole (ITC), nystatin (NYC), fluconazole (FLC), and caspofungin (CAS) were evaluated using the CLSI broth microdilution method. The prevalence of OC in the sampled population was found to be 29%. The susceptibility profile of Candida spp. revealed remarkable sensitivity, with 100% and 99% of isolates susceptible to NYC and AMB, respectively. However, concerning levels of resistance or non-wild-type minimum inhibitory concentrations (MICs) were observed, with 13.2% of Candida isolates showing resistance to FLC, 13.2% to ITC, and 16.3% to CAS. Notably, 35.2% of patients showed mixed yeast species, while 5.1% of Candida isolates exhibited multidrug resistance. The analysis of the uncommon yeast species showed that the overall frequencies of the highest MICs were observed for CAS. Furthermore, within the six non-Candida species identified, Hanseniaspora opuntiae and one isolate of Pichia kluyveri exhibited resistance to FLC and ITC, respectively, while all non-Candida species were susceptible to AMB and NYC. Additionally, one isolate of Pichia kluyveri exhibited simultaneously high MICs to two drugs ITC and CAS. Furthermore, the Hanseniaspora opuntiae isolate showed high MICs to CAS and FLC. The findings from the present study suggest that AMB and NYC can be suitable choices for empiric treatment of both common Candida species and uncommon yeast infections in substance abuse patients.